2007
DOI: 10.1111/j.1365-2389.2007.00900.x
|View full text |Cite
|
Sign up to set email alerts
|

MIOR: an individual‐based model for simulating the spatial patterns of soil organic matter microbial decomposition

Abstract: An individual-based model, called MIOR, was designed to assess hypotheses on the effect of the spatial distribution of organic matter and microbial decomposers on soil carbon and nitrogen dynamics. Two main types of object were defined to represent the decomposers and the soil organic substrates. All these objects were positioned in a 3D space. The exchange of carbon and nitrogen between these various entities was simulated. Two scenarios were tested according to the degrees of clustering of organic matter and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 34 publications
(43 reference statements)
2
26
0
Order By: Relevance
“…Coarsely, models of SOM decay can be grouped into two categories: those that are spatially explicit, and those that implicitly treat the factors influencing SOM decay as spatially homogeneous. The first category comprises models such as reactive transport models, often invoked by engineers or hydrologists (Masse et al, 2007;Scheibe et al, 2009), while the second category is more familiar to ecologists (Schimel and Weintraub, 2002;Allison, 2005;Allison et al, 2010;Davidson et al, 2012;Manzoni et al, 2012a;Moorhead et al, 2012;Moyano et al, 2013 The literature values for apparent E a are shown at the pH at which the reaction was actually observed, and does not necessarily correspond to the pH of the soils from which the samples were taken. See Sect.…”
Section: Using Experimental Advances To Enhance Recent Theoretical Efmentioning
confidence: 99%
See 1 more Smart Citation
“…Coarsely, models of SOM decay can be grouped into two categories: those that are spatially explicit, and those that implicitly treat the factors influencing SOM decay as spatially homogeneous. The first category comprises models such as reactive transport models, often invoked by engineers or hydrologists (Masse et al, 2007;Scheibe et al, 2009), while the second category is more familiar to ecologists (Schimel and Weintraub, 2002;Allison, 2005;Allison et al, 2010;Davidson et al, 2012;Manzoni et al, 2012a;Moorhead et al, 2012;Moyano et al, 2013 The literature values for apparent E a are shown at the pH at which the reaction was actually observed, and does not necessarily correspond to the pH of the soils from which the samples were taken. See Sect.…”
Section: Using Experimental Advances To Enhance Recent Theoretical Efmentioning
confidence: 99%
“…There are two approaches widely employed in other fields that could be used for coarse graining SOM dynamics. One is to start with individual dynamics, as in Masse et al (2007), and then derive the dynamics of the aggregate, in this case the entire soil profile, from the individual level dynamics. Durrett and Levin (1994) refer to this as deriving a hydrodynamic limit because of the analogous derivation of Navier-Stokes equations from the mass transfer for individual parcels of liquid.…”
Section: Using Experimental Advances To Enhance Recent Theoretical Efmentioning
confidence: 99%
“…In previous version of our model (Monga et al, 2008), we modelled organic matter decomposition using an offer-demand approach (Masse et al, 2007). We assumed that, depending on the minimum values of the degradation rate of solid organic matter or microbial growth rate (both expressed in C units), one of these two kinetics was dominating the decomposition rate.…”
Section: Mosaic II Modelmentioning
confidence: 99%
“…Among them, lattice-Boltzmann models (LBM) [29,20] are able to describe water, solute, and particulate transport in the interstitial space of soils, as well as the shape of air-water interfaces [13,53], without having to invoke the kind of simplifying assumptions about the geometry or topology of soil pores that were typical of earlier generations of models, based on traditional partial differential equations or capillary network idealizations. Similarly, agent-or individual-based models describe quantitatively the growth and metabolism of microorganisms much more realistically than traditional models, based on descriptions of population dynamics, and are able to account in great detail for the effects of the relative spatial distributions of fungi [13], bacteria [27,30,18,15], and the organic matter on which they feed. At the moment, the development of each of these different models is moving forward, in parallel with interdisciplinary efforts to combine them in order to describe various types of micro-scale scenarios and assess the nature of emergent properties of soil systems [13].…”
Section: Introductionmentioning
confidence: 99%